Optimizing School Management in Implementing Inclusive Education in Elementary Schools - Fatin, Najmah Zahirah; Anggraeni, Vadia Rahma; Zakkia, Imas Wilda; Fauziyah, Balqis Husniyah; ‘Aisy, Shabrina Rahadatul (Jurnal Inovasi Pembelajaran Karakter, 2024)
This study aims to thoroughly describe how school management in implementing inclusive education at the primary school level. The research approach used was descriptiveive qualitative method. Data collection was conducted using three main techniques, namely through direct observation in the field, in-depth interviews with informants, and collection of related documentation. The informants involved in this study include the principal, class teachers, home room teachers and special mentor teachers who have a direct relationship with the inclusive education process. Based on the results of the research, several important points were found: (1) The principal, who holds the position as the highest decision-maker in an educational institution, has a great influence on the direction of the policies and goals to be achieved by the institution; (2) There are various obstacles in the management of inclusive education at SDN Mentikan 1 Mojokerto since the beginning of the implementation until now. The most significant obstacle is related to financing or budgeting; (3) The efforts made by the school to overcome these problems are to identify the main problems that cannot be solved by the school it self. The problems are then reported to the relevant education office and the resource center at SLB Pertiwi, which is specifically appointed by the East Java Provincial Education Office as a reference institution to help manage the education of children with special needs.